Ethical framework for Artificial Intelligence and Digital technologies. (February 2022) - Ashok, Mona; Madan, Rohit; Joha, Anton; Sivarajah, Uthayasankar
Abstract: The use of Artificial Intelligence (AI) in Digital technologies (DT) is proliferating a profound socio-technical transformation. Governments and AI scholarship have endorsed key AI principles but lack direction at the implementation level. Through a systematic literature review of 59 papers, this paper contributes to the critical debate on the ethical use of AI in DTs beyond high-level AI principles. To our knowledge, this is the first paper that identifies 14 digital ethics implications for the use of AI in seven DT archetypes using a novel ontological framework (physical, cognitive, information, and governance). The paper presents key findings of the review and a conceptual model with twelve propositions highlighting the impact of digital ethics implications on societal impact, as moderated by DT archetypes and mediated by organisational impact. The implications of intelligibility, accountability, fairness, and autonomy (under the cognitive domain), and privacy (under the information domain) are the most widely discussed in our sample. Furthermore, ethical implications related to the governance domain are shown to be generally applicable for most DT archetypes. Implications under the physical domain are less prominent when it comes to AI diffusion with one exception (safety). The key findings and resulting conceptual model have academic and professional implications. Highlights: An ontological framework of digital technologies (DT). Identified digital ethics at the core of eight ethical research domains in DTs. Systematic literature review to create a taxonomy of AI digital ethics implications. Instrument outlining fourteen ethical considerations mapped to seven DT archetypes. Conceptual model of the impact of AI digital ethics implications on societal impact.